Isolation and characterization of Humic Acid from organic waste as an adsorbent for Rhodamine B - Qulub, Tatmainnul; Haniyyah AM, Nadaa; Kustomo, Kustomo; Misrochah, Nana (Journal of Natural Sciences and Mathematics Research, 2024)
Humic acid compounds are organic materials distributed across various terrestrial and aquatic ecosystems, playing a crucial role in environmental pollutant absorption. This study aims to isolate and characterize humic acid from organic waste as an adsorbent for rhodamine B. The isolation process of humic acid was conducted using the extraction method with 0.5 N NaOH solution followed by acidification using 3 M HCl solution. Characterization was carried out using a UV-Vis spectrophotometer and Fourier Transform Infrared (FTIR) spectrophotometer. The UV-Vis characterization results showed that the maximum wavelength of humic acid is 286 nm. FTIR analysis of humic acid indicates the presence of functional groups such as hydroxyl, carboxylate, and aromatic groups, consistent with the typical characteristics of humic acid. The adsorption kinetics was determined by interacting rhodamine B with humic acid after determining the optimal pH of 4, optimal time of 30 minutes, and optimal concentration of 20 ppm. The research results indicate that the adsorption kinetics of rhodamine B on humic acid follows pseudo-second-order kinetics with a reaction rate of 0.0566 min?¹ and follows the Freundlich adsorption isotherm.